Estrategia de marketing digital en el centro de belleza Dayanna López Makeup del cantón de Babahoyo periodo 2022 - López León, Liccy Dayanna (2023)
The implementation of this case study focuses on the digital marketing strategy of the Dayanna Lopez Makeup beauty center, which is aimed at the fulfillment and realization of the object of study that deals with analyzing the digitalized marketing of the business, which allowed the establishment of the investigative work variables, with the purpose of knowing the internal situation of the business, in such a way that it manages to improve advertising and positioning in the local market as well as in the minds of consumers and the Rio population in general. Therefore, the purpose of this type of analytical work is to conceptualize the variables and their factors raised in the case study, with the purpose of fulfilling and achieving the research object defined in that case of analysis. Which would allow us to have a scientific basis supported by the perspective of the population in relation to the improvements, strategies and plans that the company should implement in the establishment and thus improve its internal processes as well as its sales income. Thus, it is concluded that marketing strategies influence the development of business, because it directly affects the position of the organization in the market and in the mind of the consumer, which is why it is emphasized that the Dayanna beauty center Lopez Makeup uses digital digital marketing strategies with the purpose that allows them to improve and adequately position the company within a highly competitive and globalized commercial market.